Gender and genetic contributions to weight identity among adolescents and young adults in the U.S. (September 2016) - Wedow, Robbee; Briley, Daniel A.; Short, Susan E.; Boardman, Jason D.
Abstract: In this paper, we investigate the possibility that genetic variation contributes to self-perceived weight status among adolescents and young adults in the U.S. Using samples of identical and fraternal twins across four waves of the National Longitudinal Study of Adolescent to Adult Health (Add Health) study, we calculate heritability estimates for objective body mass index (BMI) that are in line with previous estimates. We also show that perceived weight status is heritable (h 2 ∼ 0.47) and most importantly that this trait continues to be heritable above and beyond objective BMI (h 2 ∼ 0.25). We then demonstrate significant sex differences in the heritability of weight identity across the four waves of the study, where h 2 women  = 0.39, 0.35, 0.40, and 0.50 for each wave, respectively, and h 2 men  = 0.10, 0.10, 0.23, and 0.03. These results call for a deeper consideration of both identity and gender in genetics research. Highlights: Self-assessment of weight status has genetic influences that operate above and beyond objective BMI. Genetic influences on weight identity are stronger for women compared to men. Genetic sensitivity to social cues about health and health identity is shaped in important ways by gender.